Transformasi Peran Guru Di Era Digital: Tantangan Dan Peluang - Khalisatun Husna; Farras Fadhilah; Ulfa Hayana Sari Harahap; Muhammad Arby Fahrezi; Khalid Samahangga Manik; M. Yasir Ardiansyah; Inom Nasution (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
This research aims to analyze the Transformation of Teacher Roles in the Digital Era. The method in this research is a qualitative research method with a narrative approach. Interview data was transcribed and reviewed using thematic content analysis. This study reports three important data themes which include teachers' adaptability to the digital era, challenges faced by teachers in learning in the digital era, opportunities faced by teachers in learning in the digital era and teachers' strategies in facing learning in the digital era. In this way, researchers investigate how teachers can overcome these challenges and take advantage of these opportunities to improve the quality of education in the digital era. By combining innovative approaches to teaching and investment in teacher professional development, the transformation of the teacher's role in the digital era can be a vehicle for creating more effective and inclusive learning experiences.